2020
DOI: 10.3389/fspor.2020.00086
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Disordered Eating Among International Sport Lead Rock Climbers

Abstract: Disordered eating (DE) is characterized as a range of irregular eating patterns or behaviors, which may lead to pathological eating or a clinical eating disorder diagnosis. DE patterns are associated with a variety of negative health outcomes. The prevalence of DE is highest in female athletes who participate in aesthetic or weight dependent sports. Elite rock climbers tend to be strong, small and lean, but the prevalence of DE in rock climbers is unknown. The purpose of the present study was to assess DE prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…The dietary behavior of the subjects in our study was assessed using the EAT-26 questionnaire. Results showed that 8% of the subjects exhibited an ED, a rate that is nearly identical to findings of a recent study that used a sample of 498 climbers from different countries (21). Eating disorders can lead to detrimental psychological and physiological effects and have also been linked to unhealthy physical activity behaviors and the Female Athlete Triad and/or RED-S, all of which might have a negative impact on sport performance (43).…”
Section: Discussionsupporting
confidence: 85%
“…The dietary behavior of the subjects in our study was assessed using the EAT-26 questionnaire. Results showed that 8% of the subjects exhibited an ED, a rate that is nearly identical to findings of a recent study that used a sample of 498 climbers from different countries (21). Eating disorders can lead to detrimental psychological and physiological effects and have also been linked to unhealthy physical activity behaviors and the Female Athlete Triad and/or RED-S, all of which might have a negative impact on sport performance (43).…”
Section: Discussionsupporting
confidence: 85%
“…Many sport climbers wish to have a low body mass and low body fat to enhance performance. Therefore, they may restrict calories, which can lead to inadequate macronutrient and micronutrient intake [ 22 ]. On the other hand, providing nutrients with ergogenic potential can result in energy surplus and unintended weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, 86% did not meet their target carbohydrate intake and 73% did not meet their target fat intake, whereas a large majority met or exceeded their target protein intake-a pattern that is also characteristic for many individuals with restrictive eating disorders [20]. In a 2020 survey study involving an international sample of 498 adult sport climbers, an overall 8.6% prevalence of disordered eating was observed and 4.2% of respondents reported having been treated for an eating disorder [21]. A higher prevalence of disordered eating was seen among female climbers (16.5%) compared to male climbers (6.3%); in the subgroup of elite and high elite female climbers, the prevalence was 42.9%.…”
Section: Plain English Summarymentioning
confidence: 99%